High-Frequency Data Link System Architecture Design based on SysML Modeling Language. Issue 1 (April 2021) - Haomin, Wu; Haomin, Li; Xinai, Zhang; Miao, Yu; jinze, Song
Abstract: This article is to show a new type of aircraft system design method, which decomposes the civil aircraft high-frequency data link system architecture into functional architecture, logical architecture and physical architecture, and describes the hierarchical relationship between the function, logic and physics of the system through the SysML model language.This article shows the method what converts the traditional high-frequency data link system design work based on experience and documents into model-based architecture design work.It uses the association and traceability of the model to ensure the integrity of the information in the design process and achieve the purpose of fast and convenient system design.